1988
DOI: 10.1055/s-2006-962525
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological Activity of Extracts fromPassiflora incarnata

Abstract: A fluid extract of Passiftora incarnata L. was studied for its neuropharmacologieal properties. This extract, orally and intraperitoneally administered to rats, raised the nociceptive threshold in the tail-flick and hot-plate tests, but not in the vocalization test. On intraperitoneal injection, the extract significantly prolonged sleeping time, protected animals from the convulsive effect of pentylenetetrazole, and affected locomotor activity. The fluid extract was partitioned by solvents and chromatography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
3
7

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 9 publications
1
42
3
7
Order By: Relevance
“…These results show the possibility that the differential effects of quercetin on subset of nicotinic acetylcholine receptor might be also due to different receptor subunit composition. In addition, since these nicotinic acetylcholine receptors may play an important role in modulating the neurotransmitter release or neuronal cell excitability induced by acetylcholine in pre-synaptic or post-synaptic site(s), quercetin-mediated differential regulations of subsets of nicotinic acetylcholine receptor channel activity might contribute to a diverse range of neuropharmacological effects of quercetin [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show the possibility that the differential effects of quercetin on subset of nicotinic acetylcholine receptor might be also due to different receptor subunit composition. In addition, since these nicotinic acetylcholine receptors may play an important role in modulating the neurotransmitter release or neuronal cell excitability induced by acetylcholine in pre-synaptic or post-synaptic site(s), quercetin-mediated differential regulations of subsets of nicotinic acetylcholine receptor channel activity might contribute to a diverse range of neuropharmacological effects of quercetin [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…1A) [11]. Quercetin exhibits multiple pharmacological activities in nervous and non-nervous systems [12][13][14][15][16]. However, the underlying cellular mechanisms of quercetin actions are relatively unknown, especially with regards to possible regulation of receptors or ionic channels involved in synaptic transmissions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rocha et al (2002) have suggested that orientin and isoorientin could be responsible for the observed anxiolytic-like effect of a butanolic fraction from Cecropia glazioui. However, controversial works report that pure vitexin and isovitexin showed no activity in CNS tests (Speroni and Minghetti, 1988) while orientin presented very mild anxiolytic effects (Okuyiama et al, 1996). In this work isovitexin was present in most of the active extracts (methanol, aqueous, B and C fractions).…”
Section: Discusionmentioning
confidence: 99%
“…Flavonoids and polyphones were more abundant in the leaves of P. incarnata (Table 2), the main source of these substances in the plant. [1][2][3][4][5] The antioxidant capacity of Passiflora leaves has been mentioned to be related with the content of polyphones in amount around 342.80-382.00 mg gallic acid equivalent L -1 . 7,10 However, analyses comparing the experimental treatments showed no significant difference among the flavonoid contend.…”
Section: Resultsmentioning
confidence: 99%
“…Sedative, antispasmodic and anxiolytic properties also have been described. 1,2 Clinical applications of P. incarnate are known worldwide and the species is found in the official British Herbal Pharmacopoeia since 1983, Homoeopathic Pharmacopoeia of India (1974), United States Homoeopathic Pharmacopoeia (1981), Pharmacopoeia Helvetica (1987) and the Pharmacopoeias of Egypt, France, Germany and Switzerland 3 coming to be an efficient alternative to treat several health disorders. 4 In Brazil, an extraordinary expansion of the area cultivated with P. incarnate has been observed in recent years due to the emergence of a growing interest for herbal medicines in national and international markets that are transforming P. incarnata in a promising medicinal plant.…”
Section: Introductionmentioning
confidence: 99%